2020
DOI: 10.3389/fvets.2020.554033
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Mixed-Effects Pharmacokinetic Modeling of the Novel COX-2 Selective Inhibitor Vitacoxib in Cats

Abstract: The objective of this study was to develop a non-linear mixed-effects (NLME) model to describe the disposition kinetics of vitacoxib in cats following intravenous (I.V) and oral (P.O) (single and multiple) dosing. Data from six consecutive studies with 16 healthy neutered domestic short hair cats were pooled together to build a pharmacokinetic (PK) model using NLME. Population PK parameters were estimated using the stochastic approximation expectation maximization (SAEM) algorithm implemented in Monolix 2019R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A recent study has reported that vitacoxib does not cause skin irritation in rabbits or skin sensitization in guinea pigs (9). A few other studies have reported vitacoxib pharmacokinetics in dogs (10,11), horses (12), cats (13,14) and rabbits (15). It is well known that pharmacokinetics and tissue-distribution studies are paramount in drug development (16), during which a researcher can prognosticate various issues/target organs related to drug efficacy and toxicity (17).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has reported that vitacoxib does not cause skin irritation in rabbits or skin sensitization in guinea pigs (9). A few other studies have reported vitacoxib pharmacokinetics in dogs (10,11), horses (12), cats (13,14) and rabbits (15). It is well known that pharmacokinetics and tissue-distribution studies are paramount in drug development (16), during which a researcher can prognosticate various issues/target organs related to drug efficacy and toxicity (17).…”
Section: Introductionmentioning
confidence: 99%